Customer Experience Satisfaction with Online Travel Agencies and Its Role in Promoting Sustainable Tourism Practices - Aparna Dhingra; Vipul Sharma (AG Volumes, 2026)
The rapid expansion of online travel agencies (OTAs) has transformed tourism service delivery by positioning digital platforms as key intermediaries in travel planning and booking. The present study examines customer experience satisfaction with online travel agencies and analyzes its implications for sustainable tourism and sustainable management.The study adopts a quantitative, cross-sectional research design and collects primary data through a structured questionnaire administered to OTA users. Graphical method is employed for data analysis to interpret customer perceptions related to platform experience, sustainability-oriented management practices, trust, loyalty, and behavioral intention. The findings indicate that customers generally exhibit high levels of experience satisfaction and positive perceptions of ethical and sustainable practices adopted by online travel agencies. Furthermore, the study contributes to the sustainable tourism literature by highlighting the role of sustainability-driven digital platforms in fostering long-term customer relationships and supporting sustainable tourism development.